Co-teaching in EFL classroom: lessons from collaborative teaching practice in Thailand schools - Maghfiroh, Ana; Prayitno, Harun Joko; Yusof, Norazmie; Simpol, Wanida; Suhendar, Uki; Asiyah, Siti; Yulianti, Dwiana (Intelektual Pustaka Media Utama, 2025)
Professionalism of educators is crucial for high-quality learning. To this end, the education study program implemented an internship program to provide direct experience for students (prospective teachers) and engage them in the active and ongoing process of teacher identity construction. However, the increased professionalism of prospective English teachers from this programme is still questionable. This study aimed at i) explaining the importance of collaborative teaching (co-teaching), ii) describing the practice of co-teaching between English mentor of Thai schools and Indonesian prospective teachers, and iii) exploring how co-teaching strategy develops teachers’ professionalism. It applies a descriptive qualitative approach, using observation and interviews. The subject of this study involved two English mentors and two prospective teachers who joined the internship program in Thai schools. The research findings revealed that co-teaching is very important and helpful for prospective teachers in developing teacher professionalism. In this case, English mentors and prospective teachers collaborate since planning stage, implementing the lesson plans developed, and evaluating process. As result, the collaborative teachers indicated some improvement on their pedagogical competence, social competence, and also their English competence.